Cross-talk between macrophages and gut microbiota in inflammatory bowel disease: a dynamic interplay influencing pathogenesis and therapy - Ning, Shiyang; Zhang, Zhe; Zhou, Chuan; Wang, Binbin; Liu, Zhanju; Feng, Baisui (Frontiers in Medicine, 2024)
Inflammatory bowel disease (IBD), which includes ulcerative colitis (UC) and Crohn's disease (CD), is a group of chronic immune-mediated gastrointestinal disorders. The etiology of IBD is multifactorial, involving genetic susceptibility, environmental factors, and a complex interplay between the gut microbiota and the host's immune system. Intestinal resident macrophages play an important role in the pathogenesis and progress of IBD, as well as in maintaining intestinal homeostasis and facilitating tissue repair. This review delves into the intricate relationship between intestinal macrophages and gut microbiota, highlighting their pivotal roles in IBD pathogenesis. We discuss the impact of macrophage dysregulation and the consequent polarization of different phenotypes on intestinal inflammation. Furthermore, we explore the compositional and functional alterations in gut microbiota associated with IBD, including the emerging significance of fungal and viral components. This review also examines the effects of current therapeutic strategies, such as 5-aminosalicylic acid (5-ASA), antibiotics, steroids, immunomodulators, and biologics, on gut microbiota and macrophage function. We underscore the potential of fecal microbiota transplantation (FMT) and probiotics as innovative approaches to modulate the gut microbiome in IBD. The aim is to provide insights into the development of novel therapies targeting the gut microbiota and macrophages to improve IBD management.